Forest Fires in the Brazilian Amazon and their Effects on Particulate Matter Concentration, Size Distribution, and Chemical Composition - Costa, Maria Angélica M [UNESP]; Amaral, Simone S.; Soares Neto, Turíbio G.; Cardoso, Arnaldo A. [UNESP]; Santos, José Carlos; Souza, Michele L. [UNESP]; Carvalho, João A. (Taylor & Francis, 2022)
The number of fires in the Brazilian Amazon rainforest has increased in recent years. Particulate matter emitted from these fires can affect different locations, depending on air mass trajectories. Characterization of such particles can help to analyze their effects. In the present work, particulate matter smaller than 2.5 µm from forest fires was evaluated in terms of particle size distribution, concentration, water-soluble organic compounds (WSOC), and water-soluble ions. The influence of combustion phases on the particulate matter emissions was investigated. Data were collected from a forest fire experiment conducted in the Brazilian Amazon (town of Candeias do Jamari, State of Rondônia), under real conditions, where the samples were taken directly from the smoke plume. The results showed that the concentration and diameter of the particles changed significantly depending on the combustion phase. Particle sizes ranged from 0.066 to 0.275 µm. The highest concentration of PM2.5 was found in the flaming phase (140000 μg m−3). Concentrations of sulfate, potassium, phosphate, ammonium, formate and WSOC presented significant differences when compared among the burning test and smoldering samplings. The burning test presented the highest concentration of WSOC (800 μg m−3 for the particles smaller than 0.4 μm). The potassium concentration was significantly higher during the burning test. Ions containing N, S, P, and K represented the highest percentage of particle mass. These chemical species act as macronutrients and may cause an environmental imbalance in natural forests. Furthermore, the presence of sulfate and nitrate in the analyzed samples can contribute to acid deposition.
Keywords: Amazonian deforestation fire; chemical compounds; combustion phases; particulate matter emission